1995
DOI: 10.1254/jjp.68.145
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Vasodilator Effects of the Potassium Channel Openers NIP-121 and Levcromakalim in Dogs and Rats

Abstract: ABSTRACT-The effects of potassium channel openers NIP-121 ((+)-7,8-dihydro-6,6-dimethyl-7-hydroxy-8-(2-oxo-piperidine-1-yl)-6H-pyrano[2,3 f]benz-2,1,3-oxadiazole) and levcromakalim were examined in vitro and in vivo. In isolated canine vascular beds, NIP-121 (3 x 10-9 to 10' M) and levcromakalim (3 x 10-8 to 10-6 M) produced a concentration-dependent reduction in the vasoconstrictor responses to U46619. The effects were antagonized by glibenclamide, an ATP-sensitive potassium channel blocker. The maximal relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…LKM is also a vasodilator in isolated coronary, cranial, and mesenteric arteries [14]. Herity et al [15] noted that both LKM and sodium nitroprusside reduced systemic and pulmonary vascular resistance, and mean systemic and pulmonary arterial pressures in adult pigs, the effects being greater in animals pre-treated with saline rather than (L-NAME).…”
Section: Discussionmentioning
confidence: 99%
“…LKM is also a vasodilator in isolated coronary, cranial, and mesenteric arteries [14]. Herity et al [15] noted that both LKM and sodium nitroprusside reduced systemic and pulmonary vascular resistance, and mean systemic and pulmonary arterial pressures in adult pigs, the effects being greater in animals pre-treated with saline rather than (L-NAME).…”
Section: Discussionmentioning
confidence: 99%
“…NIP-121 and cromakalim were about lo00 times less potent in the heart than on the vasculature. At pharmacologically effective doses, the cardioprotective effect of NIP-121 may be due, at least in part, to the increase of oxygen supply due to coronary vasodilation (59).…”
Section: Nip-121mentioning
confidence: 99%
“…In contrast to these agents, K + channel openers activate the channels and increase K + permeability through the cell membrane (8,18). Glibenclamide antagonizes the action of the K + channel openers: cromakalim (5,15,26,44,(55)(56)(57)(58)(59)(60)(61), pinacidil (15,44), minoxidil sulfate ( 5 9 , RP 49356 (15), nicorandil (44), and NIP-I21 (26,5658). Apparent competitive antagonism is demonstrated by the slopes of Schild plots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various kinds of K+ channels, both large conductance Ca2+-activated K+ (BK) channels and ATP-sensitive K+ (KATp) channels are reported to contribute to vasorelaxation [15,301. Yamashita et al [27], however, showed that the relaxation induced by K+ channel openers in canine basilar arteries was relatively less efficient compared with that in coronary arteries or superior mesenteric arteries.…”
Section: Introductionmentioning
confidence: 97%